The cooperation of microorganisms, bacteria, mold, yeast, and Actinomycetes consortium on decomposition of household organic waste in lowering C/N ratio - LILIS PRIHASTINI; ARI HANDONO RAMELAN; PRABANG SETYONO; PRANOTO PRANOTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Prihastini L, Ramelan AH, Setyono P, Pranoto. 2023. The cooperation of microorganisms, bacteria, mold, yeast, and Actinomycetes consortium on decomposition of household organic waste in lowering C/N ratio. Biodiversitas 24: 4862-4869. This study aimed to investigate the effective management of household waste that can lead to environmental pollution when not appropriately managed. Composting has emerged as a promising, cost-effective, and sustainable solution to address the issue of organic waste management. Furthermore, this study identified the best bioinoculants with the ability to lower the C/N ratio on the decomposition of household organic waste. It was performed with Factorial Completely Randomized Design A×B, where the A factor was bioinoculant formulas (16 formulas) and the B was the decomposition period (0, 1, 2, 3, and 4 weeks). The decomposition process was conducted at the 0, 1st, 2nd, 3rd, and 4th weeks with the C/N ratio examination. The collected data were subjected to ANOVA testing and further analyzed using the Duncan test. The results showed the lowest C/N ratio with the addition of bioinoculant code A14 (14.87) and the highest C/N reduction percentage with the addition of bioinoculant code A14 (82.7%). The best bioinoculant was treatment with A14, namely the combination of the mold consortium, yeast, and Actinomycetes. However, treatment with the addition of A14 code bioinoculant was no different from A13 code since both have the same lowercase code (i). The A13 code treatment was not significantly different from A8 since both had the same lowercase code (h).